A review of the traditional uses, phytochemical compounds, and pharmacological activities of Vallesia glabra (Cav.) Link (Apocynaceae) - Gavidia-Valencia, José G.; Llaure-Mora, Alejandrina María; Venegas-Casanova, Edmundo Arturo; Suárez-Rebaza, Luz Angélica; Rubio-López, Felipe Ruben; Rodrigo-Villanueva, Maritza; Bussmann, Rainer W.; Ganoza-Yupanqui, Mayar Luis (Ethnobotany Research and Applications, 2022)
Background: Vallesia glabra (Cav.) Link (Apocynaceae) is traditionally used in dermatological infections and as a desinflammatory. This review aims to collect information on its traditional uses, phytochemical compounds, and pharmacological activities. Methods: The scientific literature was searched in the databases Scopus, Web of Science, Alicia Repository, ScienceDirect and PubMed Central; 38 documents were selected (26 original articles, 2 review articles, 4 books and 2 theses) from 1939 to 2022. Results: V. glabra is traditionally used for pain relief, in infections and inflammations, and as an antifungal. Seventeen indole alkaloids of V. glabra have been identified, several of these alkaloids present important pharmacological activities as antimalarial and bactericidal agents demonstrated in in vitro assays. Conclusions: The traditional use of V. glabra in infections has been pharmacologically demonstrated in in vitro assays, being the terpenoid indole alkaloids, which confer the activity. Keywords: Traditional uses, phytochemical compounds, pharmacological activities, Vallesia glabra.